Developing of E-Module Diversity of Living Things Around in Improving Ereadiness of Distance Learning Students - Nuryunita Dewantari; Dwi Winarsih (Indonesian Journal of Science and Education, 2022)
This study aims to determine the feasibility of the e-module on the diversity of living things around in increasing distance learning e-readiness for students. This study uses a research and development approach. The development model used in this study is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research instruments used were pretest questions, posttest questions and questionnaires. The questionnaire used is the e-module validation questionnaire and the practicality questionnaire. The e-module validation questionnaire was filled out by experts and the practicality questionnaire was filled out by students who had used the e-module. Based on the results of the validation analysis carried out by experts, an average value of 3.74 was obtained with valid criteria, indicating that the developed e-module is feasible for use in learning. In addition, based on the results of the practicality questionnaire analysis that has been filled in by students who have used the e-module with percentage of 79.2% is obtained which means that the e-module that has been developed is practical for use in distance learning.